Non-steroidal anti-inflammatory drugs for osteoarthritis and non-specific back pain: basic provisions for effective and safe use (Interdisciplinary consensus) - A. M. Lila; N. V. Zagorodniy; L. I. Alekseeva; V. V. Afanasyev; O. I. Butranova; I. V. Guryeva; D. A. Iskra; A. E. Karateyev; T. B. Minasov; A. P. Rachin; E. A. Taskina (Современная ревматология, 2024)
The interdisciplinary council of leading experts has presented recommendations for the effective and safe use of non-steroidal anti-inflammatory drugs in osteoarthritis and non-specific back pain in general outpatient practice.